Primary Biliary Cirrhosis: Family Stories - Smyk, Daniel (SAGE-Hindawi Access to Research, 2011)
Primary biliary cirrhosis (PBC) is a chronic immune-mediated cholestatic liver disease of unknown aetiology which affects mostly women in middle age. Familial PBC is when PBC affects more than one member of the same family, and data suggest that first-degree relatives of PBC patients have an increased risk of developing the disease. Most often, these familial clusters involve mother-daughter pairs, which is consistent with the female preponderance of the disease. These clusters provide evidence towards a genetic basis underlying PBC. However, clusters of nonrelated individuals have also been reported, giving strength to an environmental component. Twin studies have demonstrated a high concordance for PBC in monozygotic twins and a low concordance among dizygotic twins. In conclusion, studies of PBC in families clearly demonstrate that genetic, epigenetic, and environmental factors play a role in the development of the disease.